1994
DOI: 10.1088/0953-4075/27/20/007
|View full text |Cite
|
Sign up to set email alerts
|

Multichannel continuum states by a least-squares approach in a spline basis: application to He and H-photoionization

Abstract: A recently proposed algorithm for the determination of the continuum wavefunction employing a 8-spline basis set expansion and a least-squares approach is extended to a full multichannel formulation employing a general close coupling expansion of the continuum wavefunction. Photoionization of the He atom up to the n = 4 threshold and Uup to the n = 3 threshold are described with a pure close coupling wavefunction (16 and 9 channels respectively), and an accurate full CI expansion for the ground state. Excellen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 68 publications
4
49
1
Order By: Relevance
“…This value of Z eff is somewhat smaller than the value 27/16 ≈ 1.69 which minimizes the ground-state energy of He in a crude independent-particle model; the smaller value is plausible because when the active electron is close to the nucleus the spectator electron is more fully screened from the nucleus. With the optical potential included, we estimate the ratio σ 2p+2s /σ 1s to be 0.578 at 250 eV compared to the values 0.509 and 0.566, respectively, predicted by Decleva et al [13] and measured by Wehlitz et al [14] Cross sections for photoionization to the 1s and to the n = 2 states of He + are shown in Figs. 1 and 2 for photon energies from 80 to 250 eV.…”
Section: Photoionization Of He With Simultaneous Excitation To He supporting
confidence: 52%
See 1 more Smart Citation
“…This value of Z eff is somewhat smaller than the value 27/16 ≈ 1.69 which minimizes the ground-state energy of He in a crude independent-particle model; the smaller value is plausible because when the active electron is close to the nucleus the spectator electron is more fully screened from the nucleus. With the optical potential included, we estimate the ratio σ 2p+2s /σ 1s to be 0.578 at 250 eV compared to the values 0.509 and 0.566, respectively, predicted by Decleva et al [13] and measured by Wehlitz et al [14] Cross sections for photoionization to the 1s and to the n = 2 states of He + are shown in Figs. 1 and 2 for photon energies from 80 to 250 eV.…”
Section: Photoionization Of He With Simultaneous Excitation To He supporting
confidence: 52%
“…The probability that the spectator electron relaxes into the 1s, rather than the 2s, state of He + is approximately | 1s,Z|1s,Z eff | 2 = 2 6 (ZZ eff ) 3 (Z + Z eff ) 6 . [13]; circles, experimental data from Bizau and Wuilleumier [15].…”
Section: Photoionization Of He With Simultaneous Excitation To He mentioning
confidence: 99%
“…A different type of grid can easily be used in different regions. In atomic physics calculation, a general grid for both bound and continuum states for arbitrary nuclear charges was introduced by Fischer [7,20] and subsequently applied successfully in the calculation of photoionization [12,21]. In the grid definition, four different parameters are introduced.…”
Section: A General Grid For Atomic Systemsmentioning
confidence: 99%
“…Because of the apparently large number of numerical operations needed to evaluate this integral accurately, they finally concluded that B-splines were not suitable for atomic structure calculations. However, there has recently been a renewed interest in the use of B-splines in complex atomic systems: Bottcher and Strayer [2] applied the B-splines to time-dependent problems, Johnson and co-workers to many-body perturbation theory [3][4][5], Fischer and co-workers [6][7][8][9] to Hartree-Fock calculations and continuum problems, Hansen and co-workers to orthogonal operators and Rydbergy series [10,11], Decleva and co-workers [12][13][14] to multichannel continuum problems, and van der Hart to R-matrix theory [15]. More detailed discussions can be found in a recent review by Sapirstein and Johnson [16].…”
Section: Introductionmentioning
confidence: 99%
“…Froese Fischer and her co-workers (Froese Fischer and Idrees, 1990;Brage et al, 1992;) had independently applied the B-splines to the continuum with success. Other earlier works employing nonrelativistic B-spline-based orbitals include calculations by Chang (1990Chang ( , 1993a, Tang et al (1990), Wang (1991a, 1991b), Tang (1991, 1992), Chen and Hsue (1992), Chen (1993), van der Hart and Hansen (1992a, 1992b, Chang and Zhen (1993), Chang and Zhu (1993), Tang and Bachau (1993), Cormier et al (1993), Xi et al (1993), and Decleva et al (1994). Extension to the relativistic conÞguration-interaction procedure was also carried out by Chen et al (1993).…”
Section: Introductionmentioning
confidence: 99%